Postpositivism and educational research : philosophy, theory, and educational research - Phillips, D. C.; Burbules, N.C. (New York : c)
Examines the problems created by the fallibility of knowledge, the inevitable value-ladenness of research, and the existence of different perspectives, showing that the pursuit of truth is still a reasonable activity.
Includes references and index
Keywords: Education -- philosophy. -- Research; Positivism